Pengembangan Kurikulum PAI Berbasis Pendidikan Kewirausahaan dalam Pendekatan Living Values Education - Sedya Sentosa; Zais Mubarok (Nusantara: Jurnal Pendidikan Indonesia, 2022)
Curriculum development occurs because of the behavioral and cultural phenomena of students in any learning activity or daily life in their environment. That a country will collapse if entrepreneurship education is not based on a basis that is not well designed in curriculum regulations in educational units. This problem needs to be learned from historical curriculum changes so that the curriculum derivative policies that are made are truly adjusted based on the needs of students. The purpose of this research is to analyze the historical approach in curriculum development in terms of entrepreneurship education. The research uses the type of library research. The results of the study seen from changes in the curriculum based on entrepreneurship education are very important in terms of literature sources that a nation will be better educated from entrepreneurship education. The PAI curriculum is the center of entrepreneurship education for students and curriculum policies in the elaboration of the learning process include entrepreneurship education for students.